Laser Profiling for the Back-Side Fault Attacks: With a Practical Laser Skip Instruction Attack on AES - Breier, Jakub (2017)
Laser fault injection is one of the strongest fault injection techniques. It offers a precise area positioning and a precise timing, allowing a high repeatability of experiments. In our paper we examine possibilities of laser-induced faults that could lead to instruction skips. After the profiling phase we were able to perform an attack on the last AddRoundKey operation in AES and to retrieve the secret key with just one faulty and correct ciphertext pair. Our experiments show very high degree of repeatability and 100% success rate with correct laser settings.